The Importance of Continuous Organizational Project Risk Management and the Value of Project Management Certificates in the Customers’ Eyes - Simon, Dániel; Reicher, Regina (International Journal of Engineering and Management Sciences, 2024)
In an increasingly complex and volatile business environment, organizational project risk management plays a critical role in determining the chances of project success. Project management has become a common tool in the hands of large organizations for executing development and improving their production cycles in a more carefully planned way. However, the future is often hard to predict, and unexpected events may occur which could have been avoided with the use of the right tools and mindset. This comprehensive research study aims to showcase the importance of continuous risk management in organizations and highlight how risk management contributes to successful project outcomes. By synthesizing information from 59 high-quality publications from Scopus and Web of Science, the research describes various risk mitigation methodologies used across diverse fields, and explores potential obstacles faced by project managers when executing risk management strategies. The primary research of the study builds upon a survey conducted with 181 experienced project managers across various industries to gain deeper insights into their risk management approaches and the constraints they may encounter. Additionally, the study seeks to analyse the value of obtaining project management certificates in relationship with led projects’ length and budget. Employing SPSS, the research presents descriptive statistics, regression, and correlation calculations to further analyse the data gathered. The aim of the research is to draw attention to the significance of continuous risk management, propose effective methodologies, identify and mitigate potential challenges, and shed light on the potential benefits of having certifications in the field of project management. This study aims to present valuable knowledge for both researchers and organizations striving to better understand the field of project risk management strategies through the systematic literature review and quantitative research results presented.